2015
DOI: 10.1080/21635781.2015.1093980
|View full text |Cite
|
Sign up to set email alerts
|

Current Suicidal Ideation Among Treatment-Engaged Active-Duty Soldiers and Marines

Abstract: We examined suicidal ideation among 399 active duty Soldiers and Marines engaged in mental health treatment. Using a generalized linear model controlling for demographic and military factors, depression, and positive traumatic brain injury screen, we confirmed our hypothesis that self-report measures of current PTSD symptoms uniquely predicted suicidal ideation. The association between PTSD severity and suicidal ideation was moderated by gender with women at higher risk as PTSD severity increased. Female Soldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…Finally, present results show that the interactions between TBI burden and memory/processing speed remained significant predictors of SI even when accounting for psychiatric and postconcussive symptom severity. Previous research has consistently demonstrated that psychiatric distress is one of the strongest predictors of suicidality (Brown et al, 2000; Jakupcak et al, 2009; Pietrzak et al, 2010; Zimmerman et al, 2015), including in active duty and veteran samples with a history of TBI (Brenner et al, 2011; Bryan & Clemans, 2013); however, our findings demonstrate that other nonemotional variables, specifically TBI-related and cognitive factors, together uniquely contribute to increased suicide risk, above and beyond psychiatric factors. As such, the present results may hold important treatment implications; cognitive training or interventions that simultaneously target both cognitive dysfunction and psychiatric distress may be most appropriate for this vulnerable group.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, present results show that the interactions between TBI burden and memory/processing speed remained significant predictors of SI even when accounting for psychiatric and postconcussive symptom severity. Previous research has consistently demonstrated that psychiatric distress is one of the strongest predictors of suicidality (Brown et al, 2000; Jakupcak et al, 2009; Pietrzak et al, 2010; Zimmerman et al, 2015), including in active duty and veteran samples with a history of TBI (Brenner et al, 2011; Bryan & Clemans, 2013); however, our findings demonstrate that other nonemotional variables, specifically TBI-related and cognitive factors, together uniquely contribute to increased suicide risk, above and beyond psychiatric factors. As such, the present results may hold important treatment implications; cognitive training or interventions that simultaneously target both cognitive dysfunction and psychiatric distress may be most appropriate for this vulnerable group.…”
Section: Discussionmentioning
confidence: 99%
“…Las anteriores cifras muestran un panorama de las investigaciones en el contexto latinoamericano sobre las variables cognitivas asociadas al riesgo suicida como la depresión (42), neuroticismo (43) e inflexibilidad cognitiva (44). Estos modelos han obtenido evidencia en muestras conformadas en países como Estados Unidos, en especial en personal de las fuerzas armadas, en donde se han reportado relaciones entre IS, síntomas depresivos, estrés postraumático y género (45,46). Sin embargo, la evidencia con muestras latinas o locales ha sido escasa.…”
Section: Variables Cognitivas En Riesgo Suicidaunclassified
“…5,7 A rapidly growing body of research has identified risk factors associated with SI among service members, including sociodemographic characteristics (eg, being female, younger, older when first entering service, less educated, never married), 11 traumatic and life stressors (eg, adverse childhood experiences, military sexual trauma, combat exposure), [12][13][14][15][16] and MHDx (eg, current and lifetime posttraumatic stress disorder [PTSD] and major depressive disorder [MDD], problematic alcohol use). [17][18][19] However, it is not known whether these factors are differentially associated with SI during deployment, a time when soldiers are exposed to unique stressors and the context of threat may alter established mechanisms of suicide risk. Given the elevated risk of suicidal behaviors in middeployment, identification of risk factors during this period is critical.…”
Section: Introductionmentioning
confidence: 99%